Effect of different dance on vo, max among post Pubescent girls - Sabaananth, S. (University of Jaffna, 2013)
The purpose of this study was to find out the effect of different dance on VO, max. To achieve the purpose ninety (N=90) women dancers were selected from Jaffna, Sri Lanka, and their age were ranged between 17 and 18 years. They were classified in to Aerobic dance ((AD)(n=30, practice aerobic dance 60+15 min / day/ 3 days / week over the period of twelve weeks), Bharathanatym Dancers ((BD) (n=30, practice bharathanatyam 60£15min / day for 3 days / week over the period of twelve weeks)] and Kandyan Dancers ((KD) n=30, from Sri lanka, practice kandyan dance 60+15 min / day/ 3 days / week over the period of 12 weeks )). VO, max was assessed for all the selected subjects by Queen's step test before and after the intervention programme, and collected data were subjected to statistical treatment using analysis of covariance (ANCOVA). In all the cases 0.05 level of confidence was fixed to test the significance. When the obtained 'F' ratio was significant, Scheffe's post hog test was used to find out the paired mean difference. Within the limitations set for this study, it was concluded that aerobic, bharathanatyam, kandyan dance training significantly influence on VO, max, however aerobic dance training shows better improvement than bharathanatyam and kandyan dance.
Keywords: aerobic; bharathanatyam; kandyan dance; Vo; max